Respostas

2014-05-29T19:41:47-03:00
A) f(x)= x²-6x+5
delta= 16 -> x= -(-6) + ou - 4/2
x'= 1 x''= 5

B) y= -x²+6+7
delta=b²+4.a.c
delta= (-6)²+4.1.7
delta= 64

x= (-b +/- raiz de delta )          x= (6 +/- raiz de 64 )          x= -6 +/- 8
   -------------------------------  =>      -----------------------   =>      ------------
                 2.a                                       2.1                                 2
x'= -6 + 8                x'= 2     
     ---------  =>            ------          =>  x'= 1
          2                         2

x'' = -6 -8              x'' = -14    
     ---------- =>             --------     =>   x'' = -7
          2                           2

Espero que eu tenha ajudado .
1 5 1